Evolvable Skin Electronics by In Situ and In Operando Adaptation. (31st August 2021) - Kim, Kyun Kyu; Choi, Joonhwa; Kim, Joon‐Hong; Nam, Sangwook; Ko, Seung Hwan
Abstract: Latest developments in thin‐film electronics have put skin electronics in the limelight. Integration of multiple skin sensors and wireless power transferring ability are cardinal components for continuous acquisition of the human signals, enabling higher level of applications in wearable healthcare and AR/VR devices. Skin sensor is considerably influenced by target body parts and users where it is attached, and thus face various design adjustments for the best performance. However, most skin electronics using conventional fabrication methods have a fixed design for specific targets and users only and face great challenge when they need design changes, for it has to re‐initialize entire fabrication process even for the simplest design modification. Here, in situ and in operando adaptation (SOA) is presented, a revolutionary customizable electronic fabrication platform that allows simultaneous evolvable design modification and addition of new functionality to original skin electronics while they are in operation on a human skin. SOA renders immediate response to various user specifications possible, offering concurrent customization for various wearable and wireless applications including human physiology/motion sensors. Furthermore, SOA offers simultaneous impedance optimization in different body parts and users which enables on‐skin wireless power supply. These findings will prove a boon to the development of customizable wearable skin‐like electronics. Abstract : In situ and in operando adaptation (SOA), a customizable electronic fabrication platform, is developed which allows for evolvable functions of skin electronics. SOA renders an immediate response to various user specifications possible, offering concurrent customization for various applications including human physiology/motion sensors. Also, simultaneous impedance optimization of devices on different body parts and users enables on‐skin wireless power supply.